1998
DOI: 10.1111/1540-5885.1510016
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Out New Products Across Country Markets: An Empirical Study of Causes of Delays

Abstract: Faced with the challenge of launching a new product into numerous countries, managers may view a sequential rollout as the prudent course of action. Rather than launching the product simultaneously in diverse countries, they may believe they can reduce risk by launching first in one or two countries, and then in others. However, this strategy overlooks the interplay between timeliness in international new product rollouts (INPR) and product success. George M. Chryssochoidis and Veronica Wong explore these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(105 citation statements)
references
References 73 publications
2
103
0
Order By: Relevance
“…Researchers have only recently begun to explore the strategic responses of firms through bribery (Iriyama et al, 2016), so our understanding of its effects remains confined to several aspects, namely entry modes (Uhlenbruck et al, 2006), exports (Lee & Weng, 2013), and capital investment (Birhanu et al, 2016). In turn, I focus on a strategic aspect (i.e., introduction of new products) that is critically linked to firms' long-term performance (Banbury & Mitchell, 1995;Schoonhoven et al, 1990;Wang & Chen, 2015) and show that bribery can positively influence firms' ability to cash in on their product innovations (Chryssochoidis & Wong, 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have only recently begun to explore the strategic responses of firms through bribery (Iriyama et al, 2016), so our understanding of its effects remains confined to several aspects, namely entry modes (Uhlenbruck et al, 2006), exports (Lee & Weng, 2013), and capital investment (Birhanu et al, 2016). In turn, I focus on a strategic aspect (i.e., introduction of new products) that is critically linked to firms' long-term performance (Banbury & Mitchell, 1995;Schoonhoven et al, 1990;Wang & Chen, 2015) and show that bribery can positively influence firms' ability to cash in on their product innovations (Chryssochoidis & Wong, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Introduction of new products is an auspicious conclusion of a long-term and risky process (Katila & Ahuja, 2002) in which innovators must overcome many challenges in terms of research, development, production, and testing before hitting the markets (Danneels, 2002). Given these significant sunk costs, firms seek to avoid costly delays to the deployment of their products (Chryssochoidis & Wong, 1998) and are willing to pay for insurance (in the form of bribes) against any harmful interference in their operations (Leff, 1964;De Jong et al, 2012). While developing links with the current political elites delivers immediate benefits for firms seeking relief from bureaucracy (Li, Meng, Wang, & Zhou, 2008), in the long term, using bribery as a tool for building ties with bureaucrats provides firms with a more effective and complementary safeguard against future political changes (Darendeli & Hill, 2016) that might affect negatively their new product launches.…”
Section: Bribery and New Product Introductionsmentioning
confidence: 99%
“…For instance, Chryssochoidis and Wong (1998) and Gielens and Dekimpe (2001) argue for a simultaneous launch to minimize product failure risk due to delayed rollouts and competitive environments. However, Kalish et al (1995) argue that conditions such as long product life cycles, small size, or slow growth of a foreign market make a waterfall strategy more preferable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chryssochoidis and Wong (1998) found a positive relationship between the simultaneous launch of hightech products and profitability. Mascarenhas (1997) found that larger initial advertising budgets do not result in higher performance in international markets, implying that the firm can disperse its advertising budget, instead of focusing it on a limited number of regions.…”
Section: Pre-entry Decisionsmentioning
confidence: 99%